Biogas reforming process investigation for SOFC application. (1st July 2015) - Chiodo, V.; Galvagno, A.; Lanzini, A.; Papurello, D.; Urbani, F.; Santarelli, M.; Freni, S.
Highlights: Mathematical model of fuel processor and experimental validation was made. Simulations made to find syngas composition varying fuel processor operating conditions. Experimental tests were carried out on SOFC mono-cell to obtain polarization curves. The best conditions for SOFC/fuel processor integrated systems were defined. Abstract: In recent years, research efforts on fuel cells have been addressed on the development of multifuel reformers with particular emphasis toward the potential use of non-traditional fuels. Among these, biogas is considered very promising to be used as syngas source for fuel cell system applications. The interest on this hydrogen source is focused mainly to supply high temperature fuel cells (HTFC). This paper reports a wide experimental research investigation on SOFC device supplied by syngas produced with different biogas reforming processes (steam reforming, autothermal reforming and partial oxidation). Thermodynamic simulations have been performed to determine the reformed gas composition varying process, reaction temperature and steam to carbon – oxygen to carbon ratios. Syngas mixtures obtained were experimentally tested in order to evaluate the performance of a SOFC mono-cell. Furthermore, an analysis of the combination: fuel processor with a SOFC stack has been determined in order to assess the total energy efficiency.